PENGARUH JUICE BELIMBING MANIS ( Averrhoa Carambola Linn ) TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI DESA LEMAH PUTIH KEC. BRATI KAB. GROBOGAN - Noor Cholifah; Suyatno Suyatno; Dewi Hartinah (Universitas Muhammadiyah Kudus, 2018)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in moderate rest. Hypertensive disease can attack at any age, including the elderly. The sweet carambola (Averrhoa Carambola linn) is one of the traditional antihypertensive drugs, because it contains high potassium which is useful as a diuretic, maintaining the stability of the body electrolyte through the sodium potassium pump, reducing the amount of water and salt in the body and loosening the blood vessels, this condition helps the pressure drop blood. The purpose of this study was to determine the effect of giving sweet starfruit juice to blood pressure in the elderly in the village of Lemah Putih Kec. Brati Kab. Grobogan. This research design is quasi experiment design with the randomized pre-test post-test control group design. The sample size is 30 respondents. The results showed that based on statistic t dependent test showed p value of intervention group at blood pressure of systole sebebsar 0.03, and diastole was 0.014 (p 0,05) hence Ho was rejected which mean in intervention group there was influence of sweet starfruit juice to elderly blood pressure with hypertension. While p value of control group at systole blood pressure was 0.786, and diastole was 0.953 (p 0,05) so Ho was received which mean in the control group there was no effect of star fruit juice to blood pressure lansia with hypertension.